2001
DOI: 10.1017/s0031182001008782
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of congeneric parasites (Monogenea: Dactylogyrus) among gill microhabitats within one host species (Rutilus rutilus L.)

Abstract: Parasite aggregation within the gill arches of 1 host species (Rutilus rutilus L.) was studied in the case of 9 congeneric monogeneans belonging to the genus Dactylogyrus. Both intra- and interspecific aggregation were followed by considering gill arches as independent patches. Parasite species were found to be aggregated both intra- and interspecifically. We showed that the intensity of parasite infection was positively related to intraspecific aggregation only for the more abundant species. No relationship w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
5
20
0
Order By: Relevance
“…These figures are not unusual, and they actually match data from a range of other studies of monogenean assemblages on fish hosts (e.g. Geets et al 1997;Gutiérrez and Martorelli 1999;Gutiérrez 2001;Simkova et al 2001;Bagge et al 2004;González and Oliva 2006) and data from communities of gastrointestinal helminths in vertebrate hosts (see Fig. 9.10 in Poulin 2007).…”
Section: Discussionsupporting
confidence: 84%
“…These figures are not unusual, and they actually match data from a range of other studies of monogenean assemblages on fish hosts (e.g. Geets et al 1997;Gutiérrez and Martorelli 1999;Gutiérrez 2001;Simkova et al 2001;Bagge et al 2004;González and Oliva 2006) and data from communities of gastrointestinal helminths in vertebrate hosts (see Fig. 9.10 in Poulin 2007).…”
Section: Discussionsupporting
confidence: 84%
“…Blahoua et al (2009) also observed that C. acerbus, C. halli and Scutogyrus minus appeared to be more prevalent and more abundant in long rainy season. Our results can be explained by water temperature which is assumed to be an important factor in controlling the occurrence of Monogeneans Simkova et al, 2001). In fact, higher water temperature must have been harmful on the adult worms (Bilong and Tombi, 2005).…”
Section: Discussionmentioning
confidence: 60%
“…As a consequence, the interspecific interaction between parasites remains a rare phenomenon (Cornell 1993;Gotelli and Rohde 2002). Indeed, the parasite communities observed in the Viaur River have low levels of species richness and relative abundances compared to other European rivers (Šimková et al 2001;Kadlec et al 2003), which may be related to the high level of eutrophication of the Viaur River (Guilmet 1997;Sidall et al 1997).…”
Section: Discussionmentioning
confidence: 99%